Paul's New Creation: Vision for a New World and Community - Chun, Sejong (Lexington Books, 2023)
In Paul’s New Creation: Vision for a New World and Community, Sejong Chun presents inter(con)textual readings of Paul’s new creation passages from the perspective of the Korean immigrant church in America. Chun focuses on Paul’s new creation’s cosmic dimension and ecclesiastical character and proposes the ekklēsia as a tangible embodiment. The author suggests that Paul, as a middleman, accomplishes the collective project of the Jerusalem collection with his Gentile churches to declare independence from the Jerusalem church authority and to demonstrate God’s alternative economy against the exploitative system of the Roman Empire.